Spatial analysis of synergies and trade-offs between the Sustainable Development Goals (SDGs) in Africa - Adams Osman; Emmanuel Abeashi Mensah; Collins Adjei Mensah; Yaw Asamoah; Suleman Dauda; Kofi Adu-Boahen; Charles Atanga Adongo (Geography and Sustainability, 2022)
Challenges faced by African countries in achieving the goals of sustainable development are similar and transboundary. Previous analysis of Africa’s progress on the Sustainable Development Goals (SDGs) has largely been non-spatial, reducing the ability to find spatial relationships between countries and SDGs to help cooperation and proffer country-specific interventions. This study adopted techniques of exploratory and inferential spatial statistics to assess the successes of African countries from 2016 to 2020 in achieving the goals of sustainable development. Also, the study sought to understand how the spatial synergies and trade-offs between SDGs vary per country and time. The results revealed that spatial hotspots of countries with high SDGs scores were mostly confined to northern African countries with significant coldspots within central and eastern Africa and few patches in western and southern Africa for 2016. In 2020, the number of countries forming hotspots reduced, with Central African countries as significant cold spots. Five main spatial relationships: positive linear, negative linear, concave, convex and undefined complex, were found among countries and the SDGs. However, these spatial relationships were fluid as they changed over time and with different levels of influence from 2016 to 2020. The study concludes that generic solutions and policies by development agencies, governments, development finance instiutions and other impact investors will not be enough in achieving the SDGs because of the spatial heterogeneity of the continent. Tailored and country-specific policies based on results of spatial statistics matter.